Exploring Strategies for Linking Research and Teaching - Freestone, R.; Wood, David (2006)
The research-teaching nexus has emerged as an institutional vector of significance for Australian universities at the intersection of concerns about both teaching quality and research productivity. What are the implications of closer linkages between research and teaching for built environment education? This paper reports the outcomes of an explorator project into the research-teaching nexus in Australia. Parallel forums wereconvened in comparable built environment faculties on either side of the continent.Aftercanvassing some general contextual issues, providing relevant institutional context,and reporting on the process followed in convening these forums, the paper identifies and discusses the issues raised. The workshops were the first of their kind in Australian built environment education.